Björnars (Ursus arctos arctos) hägnutnyttjande och beteenderespons under hundträning och test : vad blir effekten om björnarna får möjlighet att lämna hundträningen? - Bäckström Maclean, Janina (SLU/Dept. of Animal Environment and Health (until 231231), 2020)
To date, no scientific research has investigated how training of dogs (Canis lupus familiaris) on captive bears affect the welfare of bears. The Swedish Animal Welfare Act (2018:1192) includes a prohibition on training animals or using animals in tests if it causes the animal to suffer. In this study, the behavioural responses of brown bears (Ursus arctos arctos) to training of dogs was investigated. The study also examined the effect of giving bears the option to leave the dog training. Behavioural observations were carried out on three female brown bears that were held for the sole purpose of training dogs. The results showed that the bears increased their enclosure usage as well as their activity during training compared to control observations that were carried out prior to training season. It should be noted that the activity was essentially represented by one bear over the course of one day, and corresponded with training sessions where the dog exhibited a lower activity level (higher proportion of registrations out of sight and lower proportion of barking). Additionally, a higher activity level of the dog corresponded with an increase in the bears focus on the dog, movements toward and away from the dog as well as stereotypic behaviour (pacing). The bear that exhibited most of the activity was the only bear that performed stereotypic behaviour. The majority (80%) of movements toward the dog consisted of charges, which in this study was defined as a fast movement, jump, or a rush of speed toward the dog. Charges in bears are thought to be motivated by frustration, irritation or fear and uncertainty. When the bears were given the option to leave the training enclosure during training, they did so on average after one minute 83% of the occasions. However, the bears returned to the training enclosure several times. It is difficult to interpret what motivated this behaviour, but it was possibly exploratory behaviour toward the dog or the training, which could be considered a positive welfare indicator. Since ...